Militant Women of a Fragile Nation - Choudry, Aziz (Labour / Le Travail, 2011)
The article reviews the book, "Militant Women of a Fragile Nation," by Malek Abisaab.
Keywords: ABISAAB, Malek; BOOKS -- Reviews; MILITANT Women of a Fragile Nation (Book); Nonfiction; Social conditions; Women employees